2002
DOI: 10.1212/wnl.59.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Sustained cholinesterase inhibition in AD patients receiving rivastigmine for 12 months

Abstract: Rivastigmine causes persistent inhibition of AChE and BuChE in CSF as well as plasma. The persistent CSF inhibition contrasts with earlier findings after long-term treatment by the reversible ChE inhibitor tacrine, which demonstrated increased AChE activity in the CSF but not in the blood. Rivastigmine's effects on the preferential up-regulation of the AChE-R isoform may have a favorable effect on disease stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 45 publications
9
121
0
1
Order By: Relevance
“…After 12 months of treatment with rivastigmine (mean dose at 12 months, 11.8 mg/d), AChE and BuChE activities decreased from baseline by 46% and 65%, respectively. 21 In comparison, 6 to 12 months of treatment with donepezil or galantamine resulted in increased AChE activity. [18][19][20] The effects of long-term donepezil and rivastigmine administration on ChE activities are depicted in Figure 1.…”
Section: Sustained Cholinesterase Inhibition During Long-term Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…After 12 months of treatment with rivastigmine (mean dose at 12 months, 11.8 mg/d), AChE and BuChE activities decreased from baseline by 46% and 65%, respectively. 21 In comparison, 6 to 12 months of treatment with donepezil or galantamine resulted in increased AChE activity. [18][19][20] The effects of long-term donepezil and rivastigmine administration on ChE activities are depicted in Figure 1.…”
Section: Sustained Cholinesterase Inhibition During Long-term Treatmentmentioning
confidence: 99%
“…10,11 Although all ChE inhibitors share the same basic mode of action (inhibition of AChE), their pharmacokinetic characteristics differ substantially ( Table I). [12][13][14][15][16][17][18][19][20][21][22][23][24] …”
Section: Cholinesterase Inhibitors: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…46 The BCHE genotype has also been evaluated as a predictor of response to ChEI therapy. Secondary analyses of a randomized controlled trial comparing rivastigmine and donepezil in moderate AD suggested that rivastigmine, a dual acetylcholinesterase and BuChE inhibitor, 47 was associated with improved outcomes compared with donepezil, which inhibits acetylcholinesterase only, in subjects younger than 75 years 48 who did not carry the BCHE-K variant. 49 Another report suggested no difference in response to donepezil or rivastigmine treatment according to BCHE genotype.…”
Section: Introductionmentioning
confidence: 99%